Unusual Clinical Presentation of Oral Dermoid Cyst - Moon, Seong-Yong; Yoon, Jung-Hoon (The Korean Journal of Oral and Maxillofacial Pathology, 2016)
Dermoid cysts represent approximately 34% of developmental cysts in the head and neck region, and they occur mostly at the midline of the floor of the mouth. However, dermoid cysts may also migrate laterally by expansion. The lesion is usually slow growing and painless, presenting as a doughy or rubbery mass that frequently retains pitting after application of pressure. The differential diagnosis for dermoid cysts includes infections, tumors, mucous extravasation phenomena and abnormalities arising during embryonic development. In this report, we present three cases of unusual oral dermoid cysts. The first case developed on the left floor of the mouth, the second case was in the left submandibular area, and the third case was in the sublingual and submental space. All lesions were removed by the intraoral approach. Histopathologic examination revealed a dermoid cyst. The cysts were lined by orthokeratinized stratified squamous epithelium, with a prominent granular cell layer. The cyst walls were composed of fibrous connective tissue that contained sebaceous glands, sweat glands, and hair follicles. KCI Citation Count: 0